O Sistema oficial de saúde na tríplice fronteira entre Brasil, Colômbia e Peru - SOUZA, Antonio Jorge Ataide (Universidade Federal do Pará, 2018)
The Amazon and border form an intriguing dyad that sharpens the curiosity of researchers as it presents specific dynamics. The Amazon border between Tabatinga, Benjamin Constant, in Brazil; Leticia in Colombia; Iceland and Santa Rosa in Peru enters in this perspective because it contains different variables from those found in other territories of the nations. In the beginning of this region the peoples that lived there formed a society, separated by their ethnic groups, languages and customs. With the arrival of the state and therefore of capital in the region, the dynamics of society changes and new values are absorbed by the Amazonian community. Therefore, in other terms, there is segregation of this society in Brazilians, Colombians and Peruvians, marked mainly by the languages of their colonizers. With the complexity of the new society in this region, complex problems arise that will require the state's strategies to solve them. In order to try to understand this social dynamics, a methodological cut was made in the field of health, where it was observed that Brazilians, Colombians and Peruvians use the official health systems available in the three frontiers to solve their health problems, disregarding the rules imposed by the respective states -nation. Through an interdisciplinary and comparative approach was obtained information, which allowed to understand in part these social relations, given the impossibility of understanding society in its fullness. It is concluded that despite the coercive forces of the state and capital that imposes political-administrative dynamics in the sense of segregation over the populations living there, their symbolic, historical, cultural ties do not recognize this segregation and consider themselves as unique peoples.